The induction of skin graft tolerance in major histocompatibility complex-mismatched or primed recipients: primed T cells can be tolerized in the periphery with anti-CD4 and anti-CD8 antibodies. - Cobbold, S; Martin, G; Waldmann, H (1990)
Mice given short courses of anti-CD4 and anti-CD8 monoclonal antibodies became tolerant of allogeneic skin grafted at the same time. Tolerance could be obtained without T cell depletion across multiple minor antigen mismatches, both in naive and primed animals, demonstrating that peripheral T cells could be tolerized, even if they had been previously activated. Where donor and recipient were incompatible across the whole major histocompatibility complex, specific tolerance could be achieved by using a combination of depleting followed by non-depleting antibodies, where each alone was unsuccessful. Although mice clearly tolerated their original skin grafts, we observed in some strain combinations that a second fresh, but genotypically identical graft, was slowly rejected. Such mice also possessed T cells which could proliferate to donor-type stimulator cells in vitro. Whatever the mechanisms, we have demonstrated that operational transplantation tolerance can be achieved with simple, non-toxic antibody therapy. The introduction of comparable tolerance-inducing regimens in clinical organ transplantation could obviate the need for long-term immunosuppression and its unfortunate side effects.